The poetry of senses: exploring semantic mediation in timbre-aroma correspondences - Zacharakis, Asterios (Frontiers in Psychology, 2025)
Cross-modal correspondences between audition and olfaction have received relatively less attention compared to other modality pairs. This study expands on previous work regarding timbre-aroma correspondences by examining the semantic mediation hypothesis, according to which cross-modal correspondences may be partly explained by the existence of common semantic qualities. In a behavioral experiment, 26 musically trained participants rated 26 complex synthetic tones and 12 aromatic stimuli across two separate blocks using a common set of semantic scales. The analysis of semantic variables identified a largely consistent organization for both modalities, condensing into three prominent clusters: [bright, fresh, sweet], [sharp, metallic], and [full, rich, warm]. Furthermore, distances between stimuli derived from semantic ratings and optimized through a genetic algorithm exhibited a strong correlation with previously estimated ground-truth distances of direct cross-modal associations. Additionally, the stimulus configuration within the semantic space generated through Multidimensional Scaling analysis exhibited notable commonalities with the organization of stimuli derived from direct timbre-aroma correspondences. Overall, this study provides compelling evidence that semantic mediation plays a significant role in shaping cross-modal correspondences between auditory and olfactory stimuli, paving the way for further exploration of the underlying semantic dimensions that connect these two modalities.